The importance of physical activity in building social bonds and maintaining children's mental health (International Seven Journal of Health Research, 2024)
Physical activity stimulates children's ability to set goals for themselves; participate in collective activities, discussing rules, values and attitudes related to collaboration, independence, responsibility and respect for individual differences. Our work aimed to identify the main health needs of children related to mental health and sports practice. The participants in this project include students in the fourth and fifth year of elementary school, teachers and management at the Escola Municipal Professora Clary Brandão Bertoncini in the municipality of Votuporanga-SP. The educational and sporting activities carried out included identifying each participant by making a badge, chair dancing, burning, pique bandeira and object hunting; in addition to these, BMI was measured in order to classify them according to their nutritional status. In addition, the PAQ-C questionnaire was used to assess the children's sporting habits. The results showed that most of the children were underweight according to their body mass index. Their preferred sports were running, cycling and futsal, and during school breaks most of the pupils run or play intensely. In addition, it was noted that most students prefer homemade food, especially pasta. It was concluded that there is a high level of adherence to sports during school time, in which they eat a balanced and healthy diet. It was also observed that those who played more team sports found it easier to create social bonds and maintain their physical and mental health.